2014
DOI: 10.1016/j.jbi.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Supervised methods for symptom name recognition in free-text clinical records of traditional Chinese medicine: An empirical study

Abstract: Clinical records of traditional Chinese medicine (TCM) are documented by TCM doctors during their routine diagnostic work. These records contain abundant knowledge and reflect the clinical experience of TCM doctors. In recent years, with the modernization of TCM clinical practice, these clinical records have begun to be digitized. Data mining (DM) and machine learning (ML) methods provide an opportunity for researchers to discover TCM regularities buried in the large volume of clinical records. There has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…Another two similar experiments, which focused on clinical finding, achieved the F-score of 0.91 [42] and 0.92 [43] respectively. The most comparable study, carried out by Wang on traditional Chinese medicine, showed a better performance (F-score of 0.951) than the results presented here [25]. One reason for the difference might be that traditional Chinese medicine record is more rigid than present days.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Another two similar experiments, which focused on clinical finding, achieved the F-score of 0.91 [42] and 0.92 [43] respectively. The most comparable study, carried out by Wang on traditional Chinese medicine, showed a better performance (F-score of 0.951) than the results presented here [25]. One reason for the difference might be that traditional Chinese medicine record is more rigid than present days.…”
Section: Discussioncontrasting
confidence: 51%
“…Besides, the terminology-based recognition methods were popular if the dictionaries (such as SCT or UMLS) are easy to include [23, 24]. For lacking of effective Chinese clinical nomenclature, Wang [25] compared three models (the CRF, HMM and MEMM) for the task of symptom name recognition in traditional Chinese clinical records. It also indicated that the CRF outperforms the other two methods.…”
Section: Introductionmentioning
confidence: 99%
“…Various learning models and techniques have been widely used by NER researchers, such as the conditional random field (CRF) models (Liu & Zhou, 2013;Majumder et al, 2012), support vector machine (SVM) models (Saha et al, 2010), hidden Markov models (HMMs; Wang et al, 2014), logistic expression models (Ekbal & Saha, 2011), and maximum entropy Markov models (Saha et al, 2010). Various learning models and techniques have been widely used by NER researchers, such as the conditional random field (CRF) models (Liu & Zhou, 2013;Majumder et al, 2012), support vector machine (SVM) models (Saha et al, 2010), hidden Markov models (HMMs; Wang et al, 2014), logistic expression models (Ekbal & Saha, 2011), and maximum entropy Markov models (Saha et al, 2010).…”
Section: Rule-based Approachesmentioning
confidence: 99%
“…So far, little effort has been devoted to NER in ANs written in logographic languages, especially in Chinese. As reported, several ML-based algorithms including CRF, SVM, and maximum entropy have been used to identify symptom descriptions and pathogenic mechanisms from TCM EMRs [19]. Also, CRF has been used to identify biomedical name entities in Chinese research abstracts [20].…”
Section: Related Workmentioning
confidence: 99%